â€I Am Satisfied with My Marriageâ€: An Experience from Madurese Women who Married Early - Bawono, Yudho; Suminar, Dewi Retno; Hendriani, Wiwin (Humaniora, 2019)
This research aimed at examining ways by which Madurese women could achieve satisfaction in early marriage. This research used a qualitative research method with an interpretative phenomenological analysis (IPA). To understand the meaning of one?s experience by looking for themes from available data, IPA rested on three pillars, namely phenomenology, hermeneutics, and idiography. In this research, the researchers used semi-structured interviews to collect data and purposive homogeneous sampling. The participants involved were three married women under 18 years old who were living in Madura. The results of the research show that the three women are satisfied in their marriage. The satisfaction of their marriage can be seen from taking care of each other when sick, giving her enough money, and always happy with her husband, not far apart. Furthermore, Madurese women dissatisfaction in her marriage can be seen from anger if she is not given money and is not helped in doing household.